The isolation of bioactive compounds from Warburgia ugandensis bark: A report of albicanyl acetate, caseamemin and β-sitosterol from Warburgia species - Christopher Suh; Zelalem Gizachew (International Journal of Secondary Metabolite)
Warburgia ugandensis, which is one of the indigenous species of Ethiopia, is known for its wide range of biological activities. A series of drimane sesquiterpenoids have been isolated from the stem bark of the plant. However, there is no report on the herbicidal potential of the plant against invasive weeds like Parthenium hysterophorus. In this study, the herbicidal potential of W. ugandensis against the P. hysterophorus weed was investigated. Following the bioassay protocol, muzigadial as powerful phytotoxic compound together with other eight compounds were isolated from the EtOAc soluble portion of the ethanol extract of the bark of the plant. These compounds were identified using different physical and spectroscopic methods. The isolated compounds are albicanyl acetate (35), caseamemin (36), β-sitosterol (37), muzigadial (38), cinnamolide-3β-acetate (39), ugandensidial (40), 11α-hydroxy muzigadiolide (41), polygodial (42) and 9-deoxymuzigadial (43). The first three compounds are new to the species W. ugandensis. Furthermore, two other compounds namely heptacosanol (44) and hentriacontane (45) were also isolated from this species. In summary, the purpose of this study, to the best of my knowledge, is to provide the three initially identified compounds from the plant material and provide information on the plant's potential utility in agricultural applications.